Selective contracting and channelling patients to preferred providers: A scoping review. Issue 5 (May 2017) - Bes, Romy E.; Curfs, Emile C.; Groenewegen, Peter P.; de Jong, Judith D.
Highlights: A scoping review on selective contracting and channelling patients to contracted care providers. Selective contracting and channelling is practiced in several countries, mainly using financial incentives. Enrolees are negative about restrictions in provider choice resulting in lower trust and satisfaction. Health plan choice is crucial since some enrolees are willing to trade choice freedom for lower costs. Future research should focus on trust and how people weigh different attributes of health plans. Abstract: Selective contracting by health insurers and channelling patients to contracted providers is crucial in a health care system based on managed competition, as this should lead to better value for money delivery of healthcare. However, an important consequence for enrolees is that health insurers interfere with their choice of care provider. This scoping review aims to find out what is known about selective contracting from the enrolee's perspective. Is it being done and how do enrolees feel about the role of their health insurer in their care provider choice? A literature search was conducted, and, in addition, experts were consulted for extra information and documents. Results show that selective contracting and channelling are practised in several countries. This is mostly through negative financial incentives, which are also found to be the most effective strategy. However, enrolees are very negative about restrictions on provider choice introduced by their insurer. This results in enrolees feeling less satisfaction with, and trust in, care providers and health insurers. Choice is crucial in this respect since enrolees are more satisfied with their health plans and care providers when they have chosen them themselves. Future research should focus on the role of trust and how people weigh different attributes of health plans if selective contracting and channelling is to be implemented in a manner acceptable to enrolees.